Analyzing Code-Switching in Indonesia’s Next Top Model Season 1 Program on NET TV - Cahayani, Ni Kadek Widya; Putra, I Gde Agoes Caskara Surya (Austronesian: Journal of Language Science & Literature, 2024)
The ability of people to communicate with others using a variety of codes or languages in the related issue being talked about is well-known as code-switching. This study aims to determine how many different sorts of reasons for code-switching are utilized by the judges in “Indonesia’s Next Top Model Season 1” program on NET TV. The researchers used the theory proposed by Hoffmann (2014) entitled “an introduction to bilingualism” especially to analyze seven reasons for code switching found in life. However, researchers used the observation method in collecting the data. Several steps in observation were used, such as reading, collecting, and categorizing the data results based on the reasons for code-switching. As a result, the researchers found there are 23 (38,33%) intentions of clarifying the speech content for interlocutor data, 20 (33,33%) talking about particular topic data, 5 (8,33%) showing emphatic about something data, 4 (6,67%) expressing group identity data, 4 (6,67%) quoting somebody else data, and 3 (5,00%) interjection data, and repetition used for clarification represented by 1 (1,67%) data.